An Electronic Art Method within the Framework of Xu Shi Art Composition - Xi, Liew Jia; Thani, Wan Jamarul Imran Wan Abdullah (Universitas Negeri Semarang, 2024)
Under the background of modern scientific and technological art practice, artworks with contemporary characteristics are often created based on conventional culture and art. The important module of this study is Xu Shi, also known as the White Space technique, which is a critical component of composition and aesthetics in Chinese Ink Painting, derived from an aesthetic system in the long tradition of Chinese culture. Despite the existence of numerous scholarly investigations pertaining to the Xu Shi concept within the realm of traditional Chinese Ink Painting, there remains a significant deficiency in research focused on the practical application of Xu Shi principles in the domain of electronic art. Therefore, this study identifies the importance of Xu Shi whereas the main visual criteria for the formation of conventional Chinese Ink Painting and in what manner interpreted the form of electronic art. This research conducted practical applications to determine the viability of using Xu Shi technique to convey electronic art, which presents this adaptation as possible. The study method included formal visual analysis, mathematical calculations, and practice-led research. Through this merger, it is possible to create electronic art that provides a fresh perspective and significance of Chinese ink painting in a new background beyond the traditional context.